Cytotoxic Sesterterpenoids Isolated from the Marine Sponge Scalarispongia sp. - Lee, Yeon-Ju (Int J Mol Sci, 2014)
Eight scalarane sesterterpenoids, including four new compounds, were isolated from the marine sponge Scalarispongia sp. The structures of the new compounds were elucidated by 2D-NMR and HRMS analyses. All of the isolated compounds, with the exception of 16-O-deacetyl-12,16-epi-scalarolbutanolide, showed significant in vitro cytotoxicity (GI(50) values down to 5.2 μM) against six human cancer cell lines.